2003
DOI: 10.1080/14734220309405
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the red nucleus neurons to limb stimulation after cerebellar lesions

Abstract: Two series of experiments concerning the effects induced by unilateral cerebellar lesions on background activity and responses of red nucleus neurons contralateral to lesion sites are reported in this short review. The first series describes the effects of cerebellar cortex ablations, the second reports the results of hemicerebellectomy. The major source of input to the deep cerebellar nuclei, the Purkinje cells of the cerebellar cortex are known to be inhibitory. Removal of this influence by cerebellar cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…These reasons, along with the data presented in Table 1, suggest that a direct and/or substantial contribution to the major cerebellar phenotype by transgene-expressing noncerebellar neurons is unlikely. These noncerebellar transgene-expressing neurons receive projections from the DCN (cerebello-rubral, cerebello-thalamic, cerebello-vestibular, and cerebello-reticular pathways), however, and they may therefore indirectly modify the phenotype (3,26). The absence of neurodegeneration suggests that an electrical alteration in the DCN, the only neurons in the cerebellum expressing the transgene, is the predominant cause of the observed cerebellar ataxia.…”
Section: Resultsmentioning
confidence: 97%
“…These reasons, along with the data presented in Table 1, suggest that a direct and/or substantial contribution to the major cerebellar phenotype by transgene-expressing noncerebellar neurons is unlikely. These noncerebellar transgene-expressing neurons receive projections from the DCN (cerebello-rubral, cerebello-thalamic, cerebello-vestibular, and cerebello-reticular pathways), however, and they may therefore indirectly modify the phenotype (3,26). The absence of neurodegeneration suggests that an electrical alteration in the DCN, the only neurons in the cerebellum expressing the transgene, is the predominant cause of the observed cerebellar ataxia.…”
Section: Resultsmentioning
confidence: 97%
“…What could be the explanation for a short time course of spinal excitability changes? One of the important loops subserving the two‐way communication between the sensory and motor systems is the spino–cerebello–rubro–spinal projection system (Tarnecki, 2003). This loop is linked to the musculature by the rubral projection to spinal motoneurones.…”
Section: Discussionmentioning
confidence: 99%
“…Rubrospinal neurones receive major input from cerebellar nuclei (Courville, 1966) and show intense responses to sensory stimuli. Moreover, behavioural data indicate that the cerebello–rubral system is involved in learning and memory (Rosenfield & Moore, 1983; Tarnecki, 2003). Interestingly, the major decrease in the spontaneous firing of rubrospinal neurones, which appears after hemicerebellectomy, is reversible (Toyama et al 1967; Tarnecki, 2003), and this could participate in the transient spinal excitability changes observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling studies of cerebellar DCS indicate that the electric field (E) and the current density (J) spatial distributions occur mainly in the cerebellar cortex, with negligible spreads towards the brainstem [25]. Studies on cerebellar cortex ablation have confirmed the importance of Purkinje cell firings upon the discharges of cerebellar nuclei [27]. Such lesions cause a considerable increase in the background firing and cancel the pauses in discharges occurring in responses induced by somatosensory stimuli.…”
Section: Discussionmentioning
confidence: 99%